Justice in Judicial Decisions: A Review of the Cyanide Coffee Case (Decision Number 777/Pid.B/2016/PN.Jkt.Pst) - Sahidi, Aryan; Haryadi, Slamet; Dwiono, Sugeng (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This research examines the cyanide coffee case involving Jessica Kumala Wongso and Wayan Mirna Salihin, focusing on the aspects of justice in the judge's ruling. This case highlights the complexities of the Indonesian judicial system, particularly concerning the lack of a comprehensive autopsy, which resulted in uncertainty regarding the cause of Mirna's death. Although many witnesses were presented, none could provide direct evidence regarding Jessica's actions, leading the judge to rely on circumstantial evidence to reach a decision. This research analyzes how the judge considered the testimonies of witnesses and experts, as well as the use of existing evidence in the decision-making process. The findings indicate that while the judge endeavored to achieve justice, there were significant doubts regarding the validity of the evidence presented. These findings emphasize the importance of transparent and accountable legal procedures to ensure justice within the judicial system. This research is expected to provide insights for the development of legal practices in Indonesia and enhance public trust in the judicial system.